Anterograde Axonal Transport in Neuronal Homeostasis and Disease - Guillaud, Laurent; El-Agamy, Sara Emad; Otsuki, Miki; Terenzio, Marco (Frontiers in Molecular Neuroscience, 2020)
Neurons are highly polarized cells with an elongated axon that extends far away from the cell body. To maintain their homeostasis, neurons rely extensively on axonal transport of membranous organelles and other molecular complexes. Axonal transport allows for spatio-temporal activation and modulation of numerous molecular cascades, thus playing a central role in the establishment of neuronal polarity, axonal growth and stabilization, and synapses formation. Anterograde and retrograde axonal transport are supported by various molecular motors, such as kinesins and dynein, and a complex microtubule network. In this review article, we will primarily discuss the molecular mechanisms underlying anterograde axonal transport and its role in neuronal development and maturation, including the establishment of functional synaptic connections. We will then provide an overview of the molecular and cellular perturbations that affect axonal transport and are often associated with axonal degeneration. Lastly, we will relate our current understanding of the role of axonal trafficking concerning anterograde trafficking of mRNA and its involvement in the maintenance of the axonal compartment and disease.